Human rights, democracy, and legitimacy in a world of disorder / edited by Silja Voeneky, University of Freiburg, Gerald L. Neuman, Harvard University, Massachusetts. - Voeneky, Silja, 1969-; Neuman, Gerald L., 1952- (Cambridge University Press, 2018)
Human Rights, Democracy, and Legitimacy in a World of Disorder brings together respected scholars from diverse disciplines to examine a trio of key concepts that help to stabilize states and the international order. While used pervasively by philosophers, legal scholars, and politicians, the precise content of these concepts is disputed, and they face new challenges in the conditions of disorder brought by the twenty-first century. This volume will explore the interrelationships and possible tensions between human rights, democracy, and legitimacy, from the philosophical, legal, and political perspectives; as well as the role of these concepts in addressing particular problems such as economic inequality, catastrophic risks posed by new technologies, access to health care, regional governance, and responses to mass migration. Made up of essays arising from an interdisciplinary symposium convened at Harvard Law School in 2016, this volume will examine how these trusted concepts may bring order to the global community.